Respostas

  • Usuário do Brainly
2013-06-26T03:01:50-03:00

2\text{x}^2+7\text{x}+3=0

 

Temos que:

 

\text{x}=\dfrac{-\text{b}\pm\sqrt{\text{b}^2-4\cdot\text{a}\cdot\text{c}}}{2\cdot\text{a}}

 

Neste caso, \text{a}=2, \text{b}=7 e \text{c}=3.

 

Observe que:

 

\Delta=7^2-4\cdot2\cdot3=49-24=25

 

Como \Delta>0, a equação possui duas raízes reais distintas.

 

Temos que:

 

\text{x}=\dfrac{-7\pm\sqrt{25}}{2\cdot2}=\dfrac{-7\pm5}{4}

 

Logo, as raízes são:

 

\text{x}'=\dfrac{-7+5}{4}=\dfrac{-2}{4}=\dfrac{-1}{2}

 

\text{x}"=\dfrac{-7-5}{4}=\dfrac{-12}{4}=-3

 

Portanto, \text{S}=\{-3, \frac{-1}{2}\}.